The Old-Age Pension Household Replacement Rate in Belgium - Alessio J.G. Brown; Anne-Lore Fraikin (Global Labor Organization (GLO), 2022)
The objective of the paper is to examine the retirement behaviour of Belgian workers in one-earner households who are automatically granted a more generous old-age pension benefits replacement rate, called the household replacement rate. Following a recommendation of the Belgian Pension Reform Committee, this policy is to be suppressed for new pensioners, except for those receiving the minimum pension. We provide an ex-ante impact evaluation of such reform on both pension sustainability and adequacy measures. Specifically, we test whether the household replacement rate entails a work (dis)incentive mechanism promoting (harming) pension sustainability and furthermore, we analyse the role of the household replacement rate in old-age poverty and inequality measures. To do so, we use the survey dataset SHARE and a discrete time logistic duration model to study the link between retirement and financial retirement incentives created by the social security system. We find that the household replacement rate generates slightly higher retirement incentives through an income effect and we find that the household replacement rate plays an important role in decreasing the elderly poverty rate. Since households with asymmetrical working arrangements are often at the lowest part of the equivalized income distribution, the substantial effect of the household replacement rate on poverty measures is a motive to use such mechanism as a poverty alleviation tool. Nevertheless, we advocate that income redistribution measures should not be tied to a specific household composition and policies such as pensionable earning minima, minimum pension benefits and the inclusion of replacement income periods in the pension benefits calculation effectively serve the income redistribution goal without favouring a certain type of household over another. Overall, despite the positive poverty and distributional aspects of this policy, our analysis supports the reform proposal of removing the household replacement rate.
Keywords: J22; H31; H55; J26; 330; retirement; pension policy; Belgium; impact assessment